2013
DOI: 10.1063/1.4807917
|View full text |Cite
|
Sign up to set email alerts
|

Coherent synthesis of terahertz radiation from femtosecond laser filaments in air

Abstract: International audienceWe report on the coherent synthesis of pulsed terahertz radiation from femtosecond laser filaments organized in an array. The terahertz intensity is proportional to the square of the number of the filaments, which provides a simple method for scaling up of the terahertz energy with a powerful femtosecond laser. Moreover, directional off-axis terahertz radiation can be achieved. This paves the way for applications of this terahertz source for remote sensing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 28 publications
2
29
1
Order By: Relevance
“…Note that there is no decrease of the THz intensity within the range studied here. This differs from the results obtained in the absence of an electric field [12], where the THz intensity starts to decrease with the increase of the spatial separation between filaments. We attribute it to the different size of the intersection areas of two THz radiation patterns from each individual filament with and without external electric field.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Note that there is no decrease of the THz intensity within the range studied here. This differs from the results obtained in the absence of an electric field [12], where the THz intensity starts to decrease with the increase of the spatial separation between filaments. We attribute it to the different size of the intersection areas of two THz radiation patterns from each individual filament with and without external electric field.…”
Section: Resultscontrasting
confidence: 99%
“…Terahertz (THz) radiation from plasma in air induced by laser pulses was first demonstrated by Hamster and co-workers about 20 years ago [1]. Since then, the THz radiation from a long plasma channel, a filament, generated by an intense femtosecond laser has attracted much attention [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. For a filament formed by a single femtosecond laser pulse, the THz radiation is produced by the longitudinal plasma oscillations in the wake of the moving ionization front.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broadband ultrashort terahertz (THz) pulses are generated from the laser induced plasma by two-color pulses, and it is under intensive studies owing to the potential to produce high intensity THz field and achieve the off-site detection in air [1][2][3][4][5][6][7]. From the plasma filament pumped by the two-color laser pulses, the directional photocurrents generate the enhanced supercontinuum at the THz wavelength range with the conversion efficiency two orders larger than that from single color intense laser field [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that a 2D array of multiple plasma filaments in atmospheric density gases leads to the efficient increase of terahertz radiation emitted in the forward direction. As the number of filaments in an N × N array is augmented, the THz energy increase per unit polar angle in the central cone exceeds the standard gain factor N 2 [4,5]. The two-dimensional multiple filament array can be produced from an actu-EPJ Web of Conferences 195, 03013 (2018) https://doi.org/10.1051/epjconf/201819503013 TERA-2018 al non-ideal elliptical beam using a phase plate to introduce a phase barrier and block the interaction between the neighboring filaments.…”
mentioning
confidence: 99%